Refrigerator material, method for preparing the same, and refrigerator
By using a five-layer co-extrusion technology to prepare refrigerator materials, the problem of ABS materials lacking hydrophobicity and oil resistance has been solved. This achieves oil and hydrophobicity in refrigerator clips, reduces bacterial growth, aligns with the trend of green development, and lowers production costs.
Patent Information
- Application Number
- CN202611140983.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-11-06
AI Technical Summary
The lack of hydrophobic and oil-resistant properties in existing ABS materials often results in a large amount of water stains and dirt remaining on the shelf clips of refrigerators, making them a breeding ground for bacteria.
Refrigerator materials are prepared using a five-layer co-extrusion technology, including a recycled material layer, a reinforcing transition layer, and a hydrophobic and oil-resistant layer. By using chain extenders and compatibilizers of a specific composition in the reinforcing transition layer, the recycled material layer and the hydrophobic and oil-resistant layer are effectively bonded. Polyester hydrophobic masterbatch is added to the hydrophobic and oil-resistant layer to improve the hydrophobic properties of the material.
It significantly reduces liquid adhesion, decreases bacterial growth, improves the material's oil and hydrophobic properties, aligns with the trend of green development in home appliances, and reduces production costs.
Smart Images

Figure CN123040438A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refrigerator materials, and particularly relates to a refrigerator material, its preparation method, and a refrigerator. Background Technology
[0002] As living standards improve, consumers' demands for healthy living are increasing. They are willing to pay higher prices for truly effective health technologies, and health features have become a core factor influencing their appliance replacement decisions. Health features are becoming a "must-have" option for various home appliances. The technology itself is also upgrading, evolving from basic sterilization and purification to more advanced functions such as precise identification, dynamic analysis, and intelligent recommendations.
[0003] Currently, refrigerators primarily use ABS material. During use, the shelf clips often accumulate significant amounts of water stains and dirt, creating breeding grounds for bacteria. However, existing ABS materials lack hydrophobic and oil-resistant properties. Therefore, developing shelf clips with hydrophobic and antibacterial functions is particularly important. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is that the lack of hydrophobic and oil-resistant properties in existing ABS materials often results in a large amount of water stains and dirt remaining on the shelf clips of refrigerators. This invention proposes a refrigerator material with oil and hydrophobic properties that can reduce liquid adhesion and bacterial growth, as well as its preparation method and a refrigerator.
[0005] To solve the aforementioned technical problem, the technical solution adopted by the present invention is as follows: The present invention provides a refrigerator material for making refrigerator clips, comprising a recycled material layer, a reinforcing transition layer, and a hydrophobic and oil-resistant layer; the recycled material layer is located between two reinforcing transition layers, and the reinforcing transition layer is located between the recycled material layer and the hydrophobic and oil-resistant layer. The reinforcing transition layer includes ABS, compatibilizer, and chain extender. The chain extender is prepared by the following method: after melting the terminal diacid, the temperature is raised to 130-180℃, and a multi-group chain extender is added under continuous stirring. Then, a catalyst is added, and the reaction continues until no more bubbles are generated in the beaker, thus obtaining the chain extender.
[0006] In some embodiments, the recycled material layer comprises 80-100 parts recycled ABS resin, 5-15 parts antioxidant, 5-10 parts compatibilizer, and 3-8 parts lubricant.
[0007] In some embodiments, the hydrophobic and oil-resistant layer comprises 50-80 parts ABS, 20-50 parts polyester resin, 5-30 parts hydrophobic polyester masterbatch, and 10-30 parts compatibilizer.
[0008] In some embodiments, the polyester hydrophobic masterbatch is prepared by the following method: in-situ copolymerization of terephthalic acid, ethylene glycol or 1,4-butanediol and a hydrophobic polymer with two hydroxyl groups, adding calcium carbonate and stearic acid to the product after reaction and performing melt extrusion blending to prepare the polyester hydrophobic masterbatch.
[0009] In some embodiments, the terminal dicarboxylic acid is selected from at least one of picric acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, and dodecanoic acid; the multi-group chain extender is selected from at least one of glycidyl ether, triglycidyl isocyanurate, N-[4-(epoxyethylmethyl)phenyl]-N-(epoxyethylmethyl)epoxyethylmethylamine, N,N,N′,N′-tetraglycidyl-4,4′-diaminodiphenylmethane, 2,2'-(1,3-phenylene)dioxazoline, 2,2'-(1,4-phenylene)dioxazoline, and 2,2'-bis(2-oxazoline).
[0010] In some embodiments, the polyester resin is selected from polyethylene terephthalate and / or polybutylene terephthalate; the hydrophobic polymer with hydroxyl-terminated ends is selected from at least one of hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polycarbosilane, perfluoropolyether diol, and fluorinated copolyether diol.
[0011] In some embodiments, the compatibilizer is selected from at least one of KH-540, KH-550, KH-560, and KH-590; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 2246, antioxidant 168, antioxidant 622, antioxidant 944, antioxidant 3114, antioxidant 626, and antioxidant 618; and the lubricant is selected from at least one of paraffin wax, stearic acid, polyethylene wax, lead stearate, calcium stearate, barium stearate, and zinc stearate.
[0012] Another aspect of the present invention provides a method for preparing refrigerator material according to any of the above technical solutions, comprising: loading the raw materials of the hydrophobic and oil-resistant layer, the reinforcing transition layer and the recycled material layer into a barrel, dry mixing and drying them, and then setting co-extrusion dies at the ends of three extruders to extrude and obtain the refrigerator material.
[0013] In some embodiments, the screw extrusion temperature for extruding the hydrophobic and oil-resistant layer is 210-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; the screw extrusion temperature for extruding the reinforcing transition layer is 200-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; and the screw extrusion temperature for extruding the recycled material layer is 190-220℃, the screw speed is 200-600 r / min, and the feeding speed is 20-40 kg / h.
[0014] The present invention also provides a refrigerator, wherein the refrigerator's locking strip is made of refrigerator material according to any of the above-mentioned technical solutions.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a refrigerator material that incorporates a reinforced transition layer. The composition of this layer is defined, and the chain extender in the transition layer reacts with the end groups of recycled ABS and polyester resins to restore molecular weight, making the melt viscosity compatible with virgin ABS. This also improves the bonding strength between the two interfaces of the reinforced transition layer. Furthermore, a compatibilizer forms an organic-inorganic transition layer at the interface, eliminating microcracks at the filler-matrix interface and avoiding stress concentration points at the interlayer interface. This not only gives the material surface oil and hydrophobic properties, reducing liquid adhesion and bacterial growth, but also allows for increased use of recycled materials, aligning with the trend of greening home appliances. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the layer structure of the refrigerator material provided in an embodiment of the present invention; In the above figures: 1. Recycled material layer; 2. Reinforced transition layer; 3. Hydrophobic and oil-resistant layer. Detailed Implementation
[0017] The technical solutions in specific embodiments of the present invention will now be described in detail and completely with reference to the accompanying drawings. Obviously, the described embodiments are merely some specific implementations of the overall technical solution of the present invention, and not all implementations. Based on the overall concept of the present invention, all other embodiments obtained by those skilled in the art fall within the protection scope of the present invention.
[0018] This invention provides a refrigerator material for making refrigerator clips.
[0019] Compared to other refrigerator components, refrigerator shelf clips require materials with excellent processing properties, especially good bending performance. Furthermore, since the clips are located at the edge of the shelves, moisture, oil, and impurities from meat, seafood, and other items in the refrigerator compartment often accumulate there, leading to the growth of bacteria and viruses and posing a significant health hazard to users.
[0020] like Figure 1 As shown, the refrigerator material includes a recycled material layer 1. The recycled material layer 1 includes 80-100 parts of recycled ABS resin, 5-15 parts of antioxidant, 5-10 parts of compatibilizer, and 3-8 parts of lubricant.
[0021] It is understandable that in the recycled material layer 1, the amount of recycled ABS can be 85 parts, 90 parts, 95 parts, or any value within the range thereof; the amount of antioxidant can be 7 parts, 9 parts, 11 parts, 13 parts, or any value within the range thereof; the amount of compatibilizer can be 6 parts, 7 parts, 8 parts, 9 parts, or any value within the range thereof; and the amount of lubricant can be 4 parts, 5 parts, 6 parts, 7 parts, or any value within the range thereof.
[0022] The aforementioned recycled material layer 1 uses recycled ABS as raw material, which consumes less energy than virgin plastic, thus significantly reducing carbon emissions. This aligns with the trend of greening home appliances, and its price is also lower than that of virgin materials, effectively reducing production costs.
[0023] like Figure 1 As shown, the refrigerator material includes a hydrophobic and oleophobic layer 3. In some embodiments, the hydrophobic and oleophobic layer 3 includes 50-80 parts of ABS, 20-50 parts of polyester resin, 5-30 parts of polyester hydrophobic masterbatch, and 10-30 parts of compatibilizer.
[0024] Understandably, in the hydrophobic and oil-resistant layer 3, the amount of ABS can be 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, or any value within the range thereof; the amount of polyester resin can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, or any value within the range thereof; the amount of polyester hydrophobic masterbatch can be 10 parts, 15 parts, 20 parts, 25 parts, or any value within the range thereof; and the amount of compatibilizer can be 15 parts, 20 parts, 25 parts, or any value within the range thereof.
[0025] ABS possesses excellent mechanical properties, impact resistance, electrical properties, and ease of molding, making it a resin with high production volume, wide applications, and numerous varieties. However, its weather resistance is poor, its heat distortion temperature is low, and its resistance to organic solvents is particularly weak. The hydrophobic and oil-resistant layer 3 is constructed by compounding polyester resins with ABS resin as the matrix. By improving the compatibility between the modified and compatibilized polyester resins and ABS resin, the oil resistance of ABS resin is improved, reducing the penetration of grease into the material, decreasing the migration of internal additives, and reducing bacterial adhesion. On the other hand, hydrophobic masterbatches are added to the matrix to enhance the hydrophobic properties of the material, effectively preventing scale formation. However, effective bonding between the recycled material layer 1 and the hydrophobic and oil-resistant layer 3 remains a challenge for this material.
[0026] In some embodiments, the polyester hydrophobic masterbatch is prepared by the following method: in-situ copolymerization of terephthalic acid, ethylene glycol or 1,4-butanediol and a hydrophobic polymer with two hydroxyl groups, adding calcium carbonate and stearic acid to the product after reaction and performing melt extrusion blending to prepare the polyester hydrophobic masterbatch.
[0027] In some embodiments, the synthesis of hydrophobic masterbatch includes: in situ copolymerizing 100 parts of terephthalic acid, 50 parts of ethylene glycol or 1,4-butanediol, and 50 parts of a hydrophobic polymer with dihydroxyl ends in proportion; adding 10 parts of calcium carbonate and 5 parts of stearic acid to the product (100 parts) after reaction and performing melt extrusion blending to prepare hydrophobic masterbatch.
[0028] like Figure 1 As shown, the refrigerator material includes a reinforcing transition layer 2, which is located between the recycled material layer 1 and the hydrophobic and oil-resistant layer 3. By setting the reinforcing transition layer 2, effective bonding between the recycled material layer 1 and the hydrophobic and oil-resistant layer 3 is achieved.
[0029] To increase the amount of recycled ABS used and strengthen the interlayer bonding strength, the raw material formulations and molding processes for the recycled material layer 1, the reinforcing transition layer 2, and the hydrophobic and oil-resistant layer 3 were all improved. Regarding the raw material formulation, a chain extender with a specific composition was used in the reinforcing transition layer 2 to achieve effective bonding between the recycled material layer 1 and the reinforcing transition layer 2, preventing interface separation that could affect material performance. In terms of the molding process, a five-layer co-extrusion technology was adopted, placing the recycled material in the innermost layer and the higher-performance layer on the outermost layer. The outer layer material effectively prevents stains and other contaminants from penetrating the matrix.
[0030] The five-layer co-extrusion process can combine materials with different properties into a powerful multilayer structure through a single production step. The synergy of these materials significantly improves product strength. This process offers high design freedom, allowing for the free combination of different materials and precise control of each layer thickness; it is also highly adaptable, handling a variety of material combinations.
[0031] The reinforcing transition layer 2 comprises ABS, a compatibilizer, and a chain extender. In some embodiments, the reinforcing transition layer 2 consists of 50-80 parts of virgin ABS, 30-50 parts of recycled ABS, 2-5 parts of compatibilizer, and 5-15 parts of chain extender.
[0032] It is understandable that in the reinforcing transition layer 2, the amount of virgin ABS can be 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, or any value within the range thereof; the amount of recycled ABS can be 35 parts, 40 parts, 45 parts, or any value within the range thereof; the amount of compatibilizer can be 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, or any value within the range thereof; and the amount of chain extender can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, or any value within the range thereof.
[0033] In some embodiments, the chain extender is prepared by the following method: after melting a terminal diacid, the temperature is raised to 130-180°C, a multi-group chain extender is added under continuous stirring, followed by the addition of a catalyst, and the reaction continues until no more bubbles are generated in the beaker, thus obtaining the chain extender.
[0034] The aforementioned reinforcing transition layer 2 is mainly composed of virgin ABS and recycled ABS, with the addition of compatibilizers and chain extenders to improve interfacial bonding. The novel chain extender can react with the end groups of recycled ABS and polyester resins, restoring molecular weight and making the melt viscosity compatible with virgin ABS, while simultaneously improving the bonding strength between the two interfaces of the reinforcing transition layer 2. Furthermore, the compatibilizer forms an organic-inorganic transition layer at the interface, eliminating microcracks at the filler-matrix interface and avoiding stress concentration points at the interlayer interface. The novel chain extender added to the reinforcing transition layer 2 is a compound of terminal diacid substances and multi-functional chain extenders. Its performance advantages are mainly reflected in two aspects: firstly, the length of the terminal diacid substances in the raw materials is adjustable, adapting to polymer chain segments of different lengths in the system; secondly, this novel chain extender has a spindle-like structure, providing more reaction sites for the system.
[0035] In some embodiments, the synthesis of the chain extender includes: weighing a terminal diacid and placing it in a beaker with a magnetic stirrer, heating it to melt, and raising the temperature to 130-180°C. Under continuous stirring, slowly adding a weighed multi-functional chain extender, raising the system temperature to 130-180°C, and maintaining this temperature for 1 hour. Then, slowly adding a weighed catalyst (0.5%-1% of the raw material amount) to the beaker, stirring until homogeneous, and maintaining the system temperature between 130-180°C for 2-5 hours. When no more bubbles are generated in the beaker, the material can be discharged, plated, cooled, and pulverized to finally obtain the desired target chain extender. It is understood that the temperature during chain extender synthesis can also be any value within the range of 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, and so on.
[0036] To meet the requirements for using the aforementioned refrigerator materials in the card strip, the above technical solution employs a blending of recycled and virgin materials to prepare a five-layer structure comprising a recycled material layer 1, a reinforcing transition layer, and a hydrophobic and oil-resistant layer 3. This structure satisfies the application conditions of the component and maximizes the utilization of material performance. The oil resistance of the ABS material is improved through blending with polyester-based materials. Adding hydrophobic polyester masterbatch to the ABS / polyester resin significantly enhances the material's hydrophobic properties, enabling its use in long-term water-rich environments.
[0037] In some embodiments, the terminal dicarboxylic acid is selected from at least one of the following: iodic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, and dodecanoic acid.
[0038] In some embodiments, the multi-group chain extender is selected from at least one of glycidyl ether, triglycidyl isocyanurate, N-[4-(epoxyethylmethyl)phenyl]-N-(epoxyethylmethyl)epoxyethylmethylamine, N,N,N′,N′-tetraglycidyl-4,4′-diaminodiphenylmethane, 2,2'-(1,3-phenylene)dioxazoline, 2,2'-(1,4-phenylene)dioxazoline, and 2,2'-bis(2-oxazoline).
[0039] In some embodiments, the polyester resin is selected from polyethylene terephthalate and / or polybutylene terephthalate.
[0040] In some embodiments, the hydrophobic polymer with hydroxyl-terminated ends is selected from at least one of hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polycarbosilane, perfluoropolyether diol, and fluorinated copolyether diol.
[0041] In some embodiments, the compatibilizer is selected from at least one of KH-540, KH-550, KH-560, and KH-590.
[0042] In some embodiments, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 2246, antioxidant 168, antioxidant 622, antioxidant 944, antioxidant 3114, antioxidant 626, and antioxidant 618.
[0043] In some embodiments, the lubricant is selected from at least one of paraffin wax, stearic acid, polyethylene wax, lead stearate, calcium stearate, barium stearate, and zinc stearate.
[0044] In some embodiments, the ABS material used is Chi Mei 757K; the recycled ABS has a number average molecular weight of 100,000 g / mol, a weight average molecular weight of 180,000 g / mol, and a molecular weight distribution of 1.8; the PET material is CR-8863 from China Resources; and the PBT material is DuPont S0653.
[0045] Another aspect of the present invention provides a method for preparing refrigerator material according to any of the above technical solutions, comprising: loading the raw materials of hydrophobic and oil-resistant layer 3, reinforcing transition layer 2 and recycled material layer 1 into a barrel, dry mixing and drying them, and then setting co-extrusion dies at the ends of three extruders to extrude and obtain refrigerator material.
[0046] In some embodiments, the screw extrusion temperature for extruding the hydrophobic and oil-resistant layer 3 is 210-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; the screw extrusion temperature for extruding the reinforcing transition layer 2 is 200-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; and the screw extrusion temperature for extruding the recycled material layer 1 is 190-220℃, the screw speed is 200-600 r / min, and the feeding speed is 20-40 kg / h.
[0047] In some embodiments, the method for preparing refrigerator materials includes: loading the raw materials for the hydrophobic and oil-resistant layer 3, the reinforcing transition layer 2, and the recycled material layer 1 into barrels 1, 2, and 3 respectively, dry mixing for 3-5 minutes, then heating the barrels to 80-85°C and drying for 2-4 hours, and then using a twin-screw extruder to extrude the mixed raw materials, wherein the extrusion temperature of screw 1 is 210-240°C, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; the extrusion temperature of screw 2 is 200-240°C, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; and the extrusion temperature of screw 3 is 190-220°C, the screw speed is 200-600 r / min, and the feeding speed is 20-40 kg / h. By setting co-extrusion dies at the ends of the three extruders and simultaneously installing internal fine-tuning components in the dies to adjust the proportion of raw materials in each layer within the die, the overall uniformity of the product is improved.
[0048] The present invention also provides a refrigerator, wherein the refrigerator's locking strip is made of refrigerator material according to any of the above-mentioned technical solutions.
[0049] To provide a clearer and more detailed description of the refrigerator materials, preparation methods, and refrigerators provided in the embodiments of the present invention, the following description will be based on specific embodiments.
[0050] Example 1 (1) The chain extender was prepared according to the raw material composition and reaction conditions of the chain extender in Example 1 of Table 1. The preparation steps included: Weigh out the terminal dicarboxylic acid and place it in a beaker with a magnetic stirrer. Heat it to melt and raise the temperature to 130-180°C. While continuously stirring, slowly add the weighed multi-functional chain extender and raise the system temperature to 130-180°C, maintaining this temperature for 1 hour. Then, slowly add the weighed catalyst (0.5%-1% of the raw material amount) to the beaker, stir until homogeneous, and maintain the system temperature between 130-180°C for 2-5 hours. When no more bubbles are generated in the beaker, discharge the material, plate it, cool it, and pulverize it to obtain the desired chain extender.
[0051] (2) Prepare hydrophobic masterbatch according to the hydrophobic masterbatch raw material composition of Example 1 in Table 2.
[0052] (3) Prepare each raw material according to the raw material composition of Example 1 in Table 3. Wherein: 1) The enhanced transition layer 2 is composed of virgin ABS and recycled ABS, with the addition of a compound compatibilizer and a novel chain extender; 2) The hydrophobic and oil-resistant layer 3 is composed of 100 parts ABS, 20-100 parts polyester resin, 5-30 parts polyester hydrophobic masterbatch and 10-30 parts compatibilizer; 3) The recycled material layer 1 is made by adding recycled ABS resin, antioxidant, compatibilizer and lubricant into the barrel 2 in a certain proportion.
[0053] (4) Extrusion molding: The raw materials for the hydrophobic and oil-resistant layer 3, the reinforcing transition layer 2, and the recycled material layer 1 are respectively loaded into barrels 1, 2, and 3, and dry-mixed for 5 minutes. Then, the barrels are heated to 85°C and dried for 2 hours. The mixed raw materials are then extruded using a twin-screw extruder. The extrusion temperature of screw 1 is 230°C, the screw speed is 400 r / min, and the feeding speed is 10 kg / h. The extrusion temperature of screw 2 is 220°C, the screw speed is 400 r / min, and the feeding speed is 10 kg / h. The extrusion temperature of screw 3 is 200°C, the screw speed is 400 r / min, and the feeding speed is 30 kg / h. Co-extrusion dies are set at the ends of the three extruders, and internal fine-tuning components are simultaneously set in the dies to adjust the proportion of raw materials in each layer of the die, thereby improving the overall uniformity of the product.
[0054] Example 2 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0055] Example 3 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0056] Example 4 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0057] Example 5 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0058] Comparative Example 1 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0059] Comparative Example 2 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0060] Comparative Example 3 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0061] Comparative Example 4 Same as Example 1, except for the raw material composition and process parameters, as detailed in Tables 1, 2, and 3.
[0062] Table 1. Components and dosages used in the synthesis of the novel chain extender
[0063] Table 2 Raw materials for the preparation of hydrophobic masterbatch
[0064] Table 3 Refrigerator Material Composition
[0065] Performance testing (1) Hydrophobicity: Contact angle was tested, and the test method was in accordance with GB / T 30693-2014; (2) Oil resistance: Oil stain absorption: mass change (%) after soaking in vegetable oil at 60℃ for 2 hours; (3) Interfacial shear strength: Interfacial shear strength (IFSS): According to ASTM D2344 D2344M 22 StandardTest Method for Short "Beam Strength of Polymer Matrix Composite Materials and Their Laminates" was determined using a micro-debonding test method.
[0066] Table 4 Test Results
[0067] A comparison of the test results of Examples 2, 3, 4 and Comparative Example 1 shows that the oil resistance of the material can be adjusted by changing the amount of polyester resin. The greater the amount of polyester resin added, the better the oil resistance and the lower the oil absorption rate.
[0068] A comparison of the test results of Examples 1, 4, 5 and Comparative Example 2 shows that the hydrophobic properties of the material can be adjusted by changing the amount of hydrophobic masterbatch. The greater the amount of hydrophobic masterbatch added, the better the hydrophobic properties of the material.
[0069] A comparison of the test results of Examples 1, 2, 3 and Comparative Example 3 shows that the interfacial bonding strength of the materials can be improved by adjusting the amount of chain extender. The greater the amount of chain extender, the higher the interfacial shear strength of the materials.
Claims
1. A refrigerator material, characterized in that, For manufacturing refrigerator clips, a recycled material layer, a reinforcing transition layer, and a hydrophobic and oil-resistant layer are included; the recycled material layer is located between the two reinforcing transition layers, and the reinforcing transition layer is located between the recycled material layer and the hydrophobic and oil-resistant layer. The reinforcing transition layer comprises ABS, a compatibilizer, and a chain extender, wherein the chain extender is prepared by the following method: After melting the terminal dicarboxylic acid, the temperature is raised to 130-180℃. A multi-group chain extender is added under continuous stirring, followed by a catalyst. The reaction continues until no more bubbles are generated in the beaker, thus obtaining the chain extender.
2. The refrigerator material according to claim 1, characterized in that, The recycled material layer comprises 80-100 parts recycled ABS resin, 5-15 parts antioxidant, 5-10 parts compatibilizer, and 3-8 parts lubricant.
3. The refrigerator material according to claim 1, characterized in that, The hydrophobic and oil-resistant layer comprises 50-80 parts ABS, 20-50 parts polyester resin, 5-30 parts hydrophobic polyester masterbatch, and 10-30 parts compatibilizer.
4. The refrigerator material according to claim 3, characterized in that, The polyester hydrophobic masterbatch is prepared by the following method: in-situ copolymerization of terephthalic acid, ethylene glycol or 1,4-butanediol and a hydrophobic polymer with two-terminated hydroxyl groups is carried out, and calcium carbonate and stearic acid are added to the product after reaction for melt extrusion blending to prepare the polyester hydrophobic masterbatch.
5. The refrigerator material according to claim 1, characterized in that, The terminal dicarboxylic acid is selected from at least one of the following: azidopic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, and dodecanoic acid; the multi-group chain extender is selected from at least one of the following: glycidyl ether, triglycidyl isocyanurate, N-[4-(epoxyethylmethyl)phenyl]-N-(epoxyethylmethyl)epoxyethylmethylamine, N,N,N′,N′-tetraglycidyl-4,4′-diaminodiphenylmethane, 2,2'-(1,3-phenylene)dioxazoline, 2,2'-(1,4-phenylene)dioxazoline, and 2,2'-bis(2-oxazoline).
6. The refrigerator material according to claim 4, characterized in that, The polyester resin is selected from polyethylene terephthalate and / or polybutylene terephthalate; the hydrophobic polymer with hydroxyl-terminated ends is selected from at least one of hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polycarbosilane, perfluoropolyether diol, and fluorinated copolyether diol.
7. The refrigerator material according to claim 2, characterized in that, The compatibilizer is selected from at least one of KH-540, KH-550, KH-560, and KH-590; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 2246, antioxidant 168, antioxidant 622, antioxidant 944, antioxidant 3114, antioxidant 626, and antioxidant 618; the lubricant is selected from at least one of paraffin wax, stearic acid, polyethylene wax, lead stearate, calcium stearate, barium stearate, and zinc stearate.
8. The method for preparing the refrigerator material according to any one of claims 1-7, characterized in that, include: The raw materials for the hydrophobic and oil-resistant layer, the reinforcing transition layer, and the recycled material layer are respectively loaded into a barrel, dry-mixed, and dried. Then, co-extrusion dies are set at the ends of the three extruders to extrude the refrigerator material.
9. The method for preparing the refrigerator material according to claim 8, characterized in that, The screw extrusion temperature for extruding hydrophobic and oil-resistant layers is 210-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; the screw extrusion temperature for extruding reinforcing transition layers is 200-240℃, the screw speed is 200-600 r / min, and the feeding speed is 10-20 kg / h; the screw extrusion temperature for extruding recycled material layers is 190-220℃, the screw speed is 200-600 r / min, and the feeding speed is 20-40 kg / h.
10. A refrigerator, characterized in that, The refrigerator's locking strip is made of the refrigerator material described in any one of claims 1-7.
